2022
DOI: 10.1111/psyp.14053
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal words can modulate sentence meaning: Electrophysiological evidence from an RSVP‐with‐flanker task

Abstract: During natural reading, readers can take up some visual information from notyet-fixated words to the right of the current fixation and it is well-established that this parafoveal preview facilitates the subsequent foveal processing of the word. However, the extraction and integration of word meaning from parafoveal words and their possible influence on the semantic content of the sentence are controversial. In the current study, we recorded event-related potentials (ERPs) in the RSVP-with-flankers paradigm to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 88 publications
4
18
0
Order By: Relevance
“…If repetition of a previously fixated word triggers a cascade of processes, then repetition of preview word may involve similar processes. The results of some studies are consistent with this view (e.g., Dimigen et al, 2012 ; Li et al, 2015 ; Antúnez et al, 2021 ; Dimigen and Ehinger, 2021 ; Li et al, 2022 ). For example, Dimigen et al (2012) found effect of repetition of a word from preview beginning after the N1 peak, reaching a maximum around 250 ms in occipitotemporal cortex.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…If repetition of a previously fixated word triggers a cascade of processes, then repetition of preview word may involve similar processes. The results of some studies are consistent with this view (e.g., Dimigen et al, 2012 ; Li et al, 2015 ; Antúnez et al, 2021 ; Dimigen and Ehinger, 2021 ; Li et al, 2022 ). For example, Dimigen et al (2012) found effect of repetition of a word from preview beginning after the N1 peak, reaching a maximum around 250 ms in occipitotemporal cortex.…”
Section: Introductionsupporting
confidence: 68%
“…The EEG epochs of accepted trials were segmented around the onset of the parafoveal target word, from −200 to 1,500 ms, and baseline-corrected by subtracting a 100 ms pre-stimulus baseline. We defined an ROI of four occipitotemporal electrodes (PO9, PO7, PO8, PO10) to test the early preview positivity (e.g., Dimigen et al, 2012 ; Li et al, 2015 , 2022 ; Antúnez et al, 2021 ), and an ROI of four centroparietal locations (Cz, Pz, CP1, CP2) to test the N400 and the LPC component (e.g., Dimigen et al, 2012 ; Li et al, 2015 , 2022 ; Antúnez et al, 2021 ). The time windows of 150–250 ms, 250–450 ms and 500–800 ms after the onset of the targets in the foveal position were defined to test the preview positivity, N400, and LPC components, respectively (e.g., Grainger et al, 2006 ; Dimigen et al, 2012 ; Rommers and Federmeier, 2018 ; Antúnez et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…valid preview can also reduce N400 amplitude, shown in Li, Dimigen, et al (2022). Second, such an interaction could be plausibility driven, that is, reflect a genuine and higher level interplay between the processing of plausibility in parafoveal and foveal vision.…”
Section: N400 Windowmentioning
confidence: 95%
“…We also expected an interaction between parafoveal and foveal plausibility in the N400 window. Note again that in the current paradigm (Barber et al, 2013;Li et al, 2015), two distinct mechanisms can cause such an interaction (Li, Dimigen, et al, 2022): First, as for the preview positivity, a F I G U R E 5 Effect of preview validity on early brain response aligned to the foveal target fixation (word n). Shown are FRP waveforms at the left-posterior ROI as a function of whether the preview during the pretarget fixation consisted of the same word (valid) or a different word (invalid).…”
Section: N400 Windowmentioning
confidence: 95%